Literature Review: The Role of Education and Installation Training Solar Power Plant towards increasing teacher professional competence - Rachmandani, Hanifa; Rusmiati Hasanah, Viena; Emi, Chiara (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
Writing scientific papers is closely related to education and research. For this reason, in this research, training plays a role in understanding the increase in teacher professionalism after attending education and training. In this research, researchers studied a systematic literature review (SLR) regarding the role of education and training in installing Solar Power Plants (PLTS) in improving teachers' professional competence. The data source in this research is the Google Scholar database of 110 documents published from 2018 to 2022, filtered by applying inclusion and exclusion criteria, and 8 articles analyzed in full-text form. Based on research results with a systematic literature review, education and training can increase teacher professionalism, such as increasing interest in teaching talents, increasing teaching creativity, having a professional organization that has the authority to regulate matters related to teachers' professional duties, and teachers can make the best use of their time. -good. it is possible to improve knowledge and skills through other training. Keywords: Education and training, teacher professionalism